Experimental system for testing a superconducting motor at temperatures close to 15 K. (December 2020) - Tomkow, L.; Harca, I.M.; Machaj, K.; Smara, A.; Reis, T.; Glowacki, B.A.
Highlights: System for the research on superconducting motors. Achievable temperatures resembling hydrogen cooling. Challenging design with moving parts requiring tight connection. Possibility to obtain data on demagnetisation of superconductors in motors. Abstract: Integrating superconducting elements in an electric motor can greatly increase its power density. By doing so, lighter and more powerful machines can be produced for applications such as aviation, wind turbines and marine propulsion. Superconducting tapes can be stacked and magnetised to produce powerful trapped-flux magnets. The experimental setup was designed to allow measurements in a low temperature environment, providing tightness for the rotating part. We report on the design and construction of the setup and results from its first operation. The temperatures achieved during the experimental measurements reached 15 K, close to the actual operational temperatures of a liquid hydrogen cooled motor. The application of hydrogen onboard an aircraft is highly advantageous due to the possibility of its application as both coolant and fuel. Examination of the operation of the trapped-flux magnets at such temperatures is crucial for the understanding of the behavior of fully superconducting motors for future applications.